Why public service matters : public managers, public policy, and democracy - Durant, Robert F.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Why Public Service Matters conveys the importance, purpose, and nobility of a career as a civil servant in the United States.
Keywords: Science; Science; Science, general